Model Pembelajaran Auditory Intellectual and Repetition (AIR) dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Siti Fazriani (Nusantara: Jurnal Pendidikan Indonesia, 2022)
This research is motivated by the low learning outcomes of theme 5 material applying the properties of light and its relationship to the sense of sight on average below the minimum standard of completeness. Among the causative factors is the application of learning strategies that are not appropriate so that student learning outcomes are low. The purpose of this study was to improve student learning outcomes by applying the Auditory Intellectual and Repetition (AIR) learning model. This research is a classroom action research. The results showed that the first cycle only reached 52.38%, then increased to 66.67% at meeting 2. In the second cycle, student learning outcomes increased to 95.24%.